HCI for health and wellbeing: Challenges and opportunities. Issue 131 (November 2019) - Blandford, Ann
Highlights: A data lifecycle highlights important complementary interactions with health data. Challenges for HCI in health lie in the scale and complexity of health and care. Highlights role of digital mediating between people and medical technologies. To have impact at scale in health, HCI needs to complement other disciplines. Health and wellbeing technologies need to fit individual and care contexts. Abstract: In terms of Human–Computer Interaction, healthcare presents paradoxes: on the one hand, there is substantial investment in innovative health technologies, particularly around "big data" analytics and personal health technologies; on the other hand, most interactive health technologies that are currently deployed at scale are difficult to use and few innovative technologies have achieved significant market penetration. We live in a time of change, with a shift from care being delivered by professionals towards people being expected to be actively engaged and involved in shared decision making. Technically, this shift is supported by novel health technologies and information resources; culturally, the pace of change varies across contexts. In this paper, I present a "space" of interactive health technologies, users and uses, and interdependencies between them. Based on a review of the past and present, I highlight opportunities for and challenges to the application of HCI methods in the design and deployment of digital health technologies. These include threats to privacy, patient trust and experience, and opportunities to deliver healthcare and empower people to manage their health and wellbeing in ways that better fit their lives and values. Graphical abstract: Image, graphical abstract